O silêncio da educação escolar contemporânea frente à orientação sexual - Santos, Eduardo dos (2020)
Talking about sex education still sounds like a taboo to many subjects in society, especially today where prejudice is speaking louder and the school, as a teaching agent and also with a social role, is of fundamental importance in the intervention on this reality , but in most cases, due to numerous factors, it is not fulfilling its role. This article analyzes the need to work on sexual orientation in schools, as it is through it that one will be thinking about a more egalitarian society, capable of living and living with the differences present in it. The text, from a bibliographic research, addresses three topics: characterization of the school context in the 21st century and the issue of sexual diversity; how diversity is treated in the school context and; educational processes that help to promote school environments free from prejudice. The conclusion points out that sexual orientation is still a major challenge to be faced in school education.